2017
DOI: 10.19173/irrodl.v18i1.2643
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Academics Use Academic Social Networking Sites?

Abstract: Academic social-networking sites (ASNS) such as Academia.edu and ResearchGate are becoming very popular among academics. These sites allow uploading academic articles, abstracts, and links to published articles; track demand for published articles, and engage in professional interaction. This study investigates the nature of the use and the perceived utility of the sites for academics. The study employs the Uses and Gratifications theory to analyze the use of ASNS. A questionnaire was sent to all faculty membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 38 publications
(36 reference statements)
7
51
0
3
Order By: Relevance
“…These networks offer more transparency and support the exchange of ideas and publications (Bartling & Friesike, ). Studies found that the main motivations for using ASNSs were self‐presentation; establishing scientific contacts and interacting with peers; finding new research and publication possibilities; acquisition of professional knowledge; and getting out of institutional constraints (Bartling & Friesike, ; Jordan, ; Meishar‐Tal & Pieterse, ; NPG, ). With regard to these aspects, there is also a connection between academic online identity and formal academic institutional roles (Jordan, ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These networks offer more transparency and support the exchange of ideas and publications (Bartling & Friesike, ). Studies found that the main motivations for using ASNSs were self‐presentation; establishing scientific contacts and interacting with peers; finding new research and publication possibilities; acquisition of professional knowledge; and getting out of institutional constraints (Bartling & Friesike, ; Jordan, ; Meishar‐Tal & Pieterse, ; NPG, ). With regard to these aspects, there is also a connection between academic online identity and formal academic institutional roles (Jordan, ).…”
Section: Related Workmentioning
confidence: 99%
“…Even though the functionalities of ASNSs are aimed at work‐related academic purposes, the general functionalities are in part very similar to those of private social networks such as Facebook. Thus, ASNSs combine the characteristics of private social networks with the possibility to share publication, connect with peers, and discuss research‐related issues (Bhardwaj, ; Meishar‐Tal & Pieterse, ; Ovadia, ).…”
Section: Introductionmentioning
confidence: 99%
“…Academic social networks have been the subject of a fair amount of academic research, given their relatively recent entry into the scholarly communication landscape. A number of studies have been done on the adoption rates by researchers in a particular discipline (Muscanell & Utz, 2017;Marra, 2016;Ortega, 2015;Van Noorden, 2014;Haustein et al, 2014) or a particular country (Mikki, Zygmuntowska, Gjesdal, & Ruwehy, 2015;Campos & Valencia, 2015;Elsayed, 2015;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Meishar-Tal & Pieterse, 2017. Mikki et al (2015 found that ResearchGate was used most often by Norwegian scholars overall, though humanities scholars used Academia.edu more frequently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academics and researchers currently explore the capabilities of emergent technologies to support the learning process in an interactive learning environment. Table 1 summarizes recent relevant research on several dimensions of social networks and smart learning [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]:…”
Section: Literature Review On the Exploitation Of Social Networking Tmentioning
confidence: 99%
“…And consider challenges in its implementation as well. Learning analytics, visual learning, cloud computing and emergent wearable technologies are key drivers for the successful achievement of the benefits of the online learning process [21,22,28,38,39]. At the same time researches show that neither academia [40], nor students are fully prepared to accept the challenges and use new possibilities meaningfully to construct new knowledge.…”
Section: Literature Review On the Exploitation Of Social Networking Tmentioning
confidence: 99%